Analyzing the Impact of Artificial Intelligence (AI) Integration on the Transformation of Teachers’ Instructional Methods and Students’ Learning Experiences in Elementary Schools: - Agung Setyawan; Keisha Najwa Aqilah; Selvia Dwiyanti (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2025)
This study analyzes the impact of integrating Artificial Intelligence (AI) on the transformation of teachers’ instructional methods and students’ learning experiences in elementary schools, highlighting both the benefits and the challenges of implementation. The study employed a qualitative approach, using structured interviews with three elementary school teachers and three elementary school students, selected through purposive sampling. Data collection was conducted on 30 September (08:40–12:00) and analyzed descriptively through data reduction, categorization, and interpretation of the meaning of participants’ statements. The interview results indicate that the use of AI in elementary schools remains limited; some teachers have not directly utilized AI and instead rely more on digital media or platforms, such as YouTube, TikTok, Canva, or search engines, to enrich learning materials. In terms of impact, the use of technology was perceived to accelerate the search for learning materials, facilitate the preparation of teaching resources, and increase students’ motivation and ease in completing assignments. However, implementation also faces obstacles, including teachers’ limited digital literacy, limited facilities and internet connectivity, and unequal access to devices among students, which may widen the digital divide. These findings underscore the need to strengthen teacher capacity, enhance infrastructure support, and effectively monitor technology use so that AI can be utilized wisely in elementary education.